Pelatihan Kewirausahaan Meronce Aksesoris Manik Manik - Hasbi Hasbi; Mas’ud Uqbah Al Ansyari; Ika Wisudawaty; Herawan Hisanan; Irfan Yunus (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
The creative industry in Indonesia has grown rapidly in recent years, resulting in increasingly intense trade competition and various innovations in product marketing. This research focuses on the handicraft industry, especially in the manufacture of accessories such as bracelets, necklaces, and rings. Although the meronce looks simple, the biggest challenge is to create a unique design and ensure the strength of the connecting rope so that it doesn't break easily. Meronce accessories is an activity or process of stringing various elements into an attractive and functional whole, such as bracelets, necklaces, and rings. Usually, meronce is done by using elastic straps as a connecting medium and beads as decorations. While it looks easy and everyone can do it, not everyone has the same design idea when it comes to accessories. In addition, the challenge in meronce is the process of swallowing. We must be able to ensure that when accessories are used, the strap does not come off easily. These beaded accessories can also be a fashion support worn by someone.